2021
DOI: 10.1186/s12883-021-02148-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between electrode position of deep brain stimulation and motor symptoms of Parkinson’s disease

Abstract: Background To investigate the relationship between the position of bilateral STN-DBS location of active contacts and the clinical efficacy of STN-DBS on motor symptoms in Parkinson’s disease (PD) patients. Methods Retrospectively analyze the clinical data of 57 patients with PD who underwent bilateral STN-DBS from March 2018 to December 2018. Unified Parkinson’s Disease Rating Scale-Part III (UPDRS-III) score, levodopa equivalent day dose (LEDD), P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 25 publications
4
30
1
Order By: Relevance
“…As mentioned in our previous article [5], UPDRS-III scores (Medication-off) were improved (55.42%), the PDQ-39 scores were improved (47.39%) and the LEDD had decreased by 40.08% at 6 months after surgery. The improvement rate of HAMA scores and HAMD scores of 57 patients was [41.7(34.9) %;37.5(33.4) % respectively (both P<0.001)].…”
Section: Clinical Outcomessupporting
confidence: 66%
See 3 more Smart Citations
“…As mentioned in our previous article [5], UPDRS-III scores (Medication-off) were improved (55.42%), the PDQ-39 scores were improved (47.39%) and the LEDD had decreased by 40.08% at 6 months after surgery. The improvement rate of HAMA scores and HAMD scores of 57 patients was [41.7(34.9) %;37.5(33.4) % respectively (both P<0.001)].…”
Section: Clinical Outcomessupporting
confidence: 66%
“…Between March and December 2018, a total of 57 subjects were hospitalized at the Department of Neurosurgery of the Beijing Tiantan Hospital a liated to Capital Medical University, the First Hospital of Hebei Medical University and General Hospital of Ningxia Medical University for optimizing a previously performed STN-DBS, As mentioned in our previous article [5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1D). While the VTA estimation was not validated by another method, prior studies in Parkinson's disease [36,37], essential tremor [38], and dystonia [39] have shown a good correlation between VTA overlap with target structure and clinical outcomes.…”
Section: Volumetric Overlap Between Vta and Gpimentioning
confidence: 99%